Pengaruh Motivasi Belajar Siswa terhadap Hasil Belajar Mata Pelajaran Matematika Siswa Kelas VII MTs Muhammadiyah 2 Jenangan - Putri Aisa Nur Fajar; Uki Suhendar; Dwi Avita Nurhidayah (EduInovasi: Journal of Basic Educational Studies, 2026)
Education and learning are two concepts that are closely related to individual development. Education provides a framework and environment that allows learning to occur effectively, with a curriculum that supports learning methods according to student needs. In MTs Muhammadiyah 2 Jenangan, mathematics is often considered difficult by students, so high motivation is needed during the learning process. Lack of motivation can negatively impact academic achievement. Teachers are required to create a fun and effective learning atmosphere, as well as encourage students' curiosity about the material taught. Based on this, the researcher conducted research with a quantitative method. This study aims to analyze the influence of learning motivation on the learning outcomes of grade VII students at MTs Muhammadiyah 2 Jenangan. This study uses a quantitative method with the distribution of questionnaires to 75 students as the variables of learning motivation (X) and learning outcomes (Y) to determine the final exam scores of even semesters of mathematics lessons. The data were analyzed using simple linear regression with the help of SPSS version 27. The results showed that there was a significant positive influence between learning motivation and student learning outcomes, with the regression equation Y = -74.432 + 1.849X. The regression coefficient value of 1.849 shows that each increase in learning motivation will increase learning outcomes by 1.849 points. The significance test showed a t-count value of 13.751 ≥ a t-table of 1.665, which indicated that the null hypothesis (H0) was rejected and the alternative hypothesis (H1) was accepted. Overall, learning motivation contributed 72.1% to student learning outcomes, while the remaining 27.9% was influenced by other variables that were not studied.